2017
DOI: 10.1016/j.omtn.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Human DMBT1-Derived Cell-Penetrating Peptides for Intracellular siRNA Delivery

Abstract: Small interfering RNA (siRNA) is a promising molecule for gene therapy, but its therapeutic administration remains problematic. Among the recently proposed vectors, cell-penetrating peptides show great promise in in vivo trials for siRNA delivery. Human protein DMBT1 (deleted in malignant brain tumor 1) is a pattern recognition molecule that interacts with polyanions and recognizes and aggregates bacteria. Taking advantage of these properties, we investigated whether specific synthetic DMBT1-derived peptides c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Absence of the protein or glycosylation has been described in cancer [183][184][185][186], while roles for post-translational deimination in its multifaceted functions remain unknown. This may be of particular interest as DMBT1 shows a pattern recognition activity for poly-sulfated and poly-phosphorylated ligands, including nucleic acids, and also has the ability to aggregate ligands-properties which have made it a protein of interest for targeted nano-delivery [187]. Therefore, indication of structural changes of this protein via post-translational deimination may be of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of the protein or glycosylation has been described in cancer [183][184][185][186], while roles for post-translational deimination in its multifaceted functions remain unknown. This may be of particular interest as DMBT1 shows a pattern recognition activity for poly-sulfated and poly-phosphorylated ligands, including nucleic acids, and also has the ability to aggregate ligands-properties which have made it a protein of interest for targeted nano-delivery [187]. Therefore, indication of structural changes of this protein via post-translational deimination may be of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…Various, creative strategies have been employed to surmount these barriers. Electrostatic charge interaction between cationic CPPs and negatively charged siRNAs have produced self-assembly of CPPs and siRNA into nanoparticles [96][97][98][99]. Escape from endosomal compartments has been achieved by acylation [99], stearylation [100] or histidine modification [101] of the N-terminus of CPPs.…”
Section: Small Interfering Rnamentioning
confidence: 99%
“…Also, the study by Stoddard and colleagues demonstrated that transport of HIV-1 can be inhibited by antibodies or peptides that block the interaction of DMBT1 with the HIV-1 envelope protein gp120 58 . Given our findings on DMBT1 expression in lung AT2 cells and its co-expression with ACE2, as well as its reported binding with multiple viruses, we suggest that targeting DMBT1, whether by adding soluble DMBT1-derive peptides 59 among all lung cell subsets AT2 cells displayed highest relative expression of the SARS-CoV-2 receptor ACE2, albeit at a low cell fraction (~2.2% of all AT2 cells). We found that the viral scavenger DMBT1 is highly expressed in AT2 cells and correlates with ACE2 in this compartment.…”
Section: Discussionmentioning
confidence: 52%